Rafad - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
RAFAD (Recherches et applications de financements alternatifs au developpement) is a Swiss private international foundation. Its mission is to contribute to Third World development while avoiding creating the dependency associated with traditional...